2016
DOI: 10.1186/s12868-016-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

Molar loss and powder diet leads to memory deficit and modifies the mRNA expression of brain-derived neurotrophic factor in the hippocampus of adult mice

Abstract: BackgroundIt is known that tooth loss is known to be a risk factor for Alzheimer’s disease and soft diet feeding induces memory impairment. Recent studies have shown that brain-derived neurotrophic factor (BDNF) is associated with tooth loss or soft diet in young animal model, and that BDNF expression is decreased in patients with Alzheimer’s disease. However, single or combined effect of tooth loss and/or soft diet on brain function has not fully understood. Here we examined the effect of molar loss and powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…The hippocampal BDNF levels are involved in the regulation of the hippocampal neurogenesis and synaptic plasticity [11,33]. Animal studies indicated that tooth loss decreased hippocampal BDNF expression levels both in C57BL/6J and SAMP8 mice [11,33]. We consider that the effect of tooth loss on the hippocampus was similar for genetically different inbred murine strains.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The hippocampal BDNF levels are involved in the regulation of the hippocampal neurogenesis and synaptic plasticity [11,33]. Animal studies indicated that tooth loss decreased hippocampal BDNF expression levels both in C57BL/6J and SAMP8 mice [11,33]. We consider that the effect of tooth loss on the hippocampus was similar for genetically different inbred murine strains.…”
Section: Discussionmentioning
confidence: 91%
“…Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family, which is widely expressed in the brain. The hippocampal BDNF levels are involved in the regulation of the hippocampal neurogenesis and synaptic plasticity [11,33]. Animal studies indicated that tooth loss decreased hippocampal BDNF expression levels both in C57BL/6J and SAMP8 mice [11,33].…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies have supported the hypothesis that cognitive decline is associated with masticatory dysfunction. These studies have demonstrated that cognitive decline is related to cellular and neurochemical change in the hippocampus, including decreased cellular proliferation [ 47 , 48 , 50 ], decreased levels of brain-derived neurotrophic factor [ 44 , 47 , 59 ], as well as increased nitrous oxide levels [ 55 ] and extracellular dopamine levels [ 52 ]. These findings suggested that the hippocampus-dependent deficits in learning and memory may contribute to the association between cognitive decline and masticatory dysfunction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that the hippocampus-dependent deficits in learning and memory may contribute to the association between cognitive decline and masticatory dysfunction [ 10 ]. Importantly, using animal models, researchers were able to investigate the interactional effect between masticatory dysfunction and other factors, such as the type of diet [ 46 , 59 ], environmental stimuli [ 47 ], and stress [ 52 ]. These factors can partially ameliorate the cognitive deficits induced by masticatory dysfunction [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study does not answer age‐related deficits in learning and memory similar to those seen in elderly humans, since we created disease models in intact mice and the behavioural test battery was consisted of a single open‐field test. To understand clinically relevant situations, more specific experimental settings such as experimental murine model for human senile dementia, longer neurobehavioural assessments of spatial learning ability to cause cognitive impairment, and pathological/molecular‐based preparations to validate hippocampal neuron loss should be proposed in future studies.…”
Section: Discussionmentioning
confidence: 99%